Conservation assessment at a regional level: the study case of 'Delphinium fissum' subsp. 'sordidum' (Ranunculaceae), an endemic Iberian subspecies with disjunct distribution - Ramírez-Rodríguez, Ruben; Amich, Francisco (Mediterranean Botany, 2019)
Delphinium fissum subsp. sordidum is a restricted endemic subspecies whose core distribution is located in the central-western Iberian Peninsula with a disjunct subpopulation in Sierra Mágina (Jaén Province). This article reports a detailed study of its current distribution, population size and structure, and the threats that it faces. Phytosociological analysis shows two main plant communities where D. fissum subsp. sordidum develops: Quercion pyrenaicae and Quercion broteroi. According to the most recent IUCN categories and criteria, the conservation status of D. fissum subsp. sordidum is “Endangered” (EN) in Castile and Leon. We propose the creation of a Plant Micro-Reserve (PMR) in an enclave with high geological, ecological and conservation values. Medium-long term and individualized monitoring programs are required for all distribution range of Delphinium fissum subsp. sordidum. An overall Recovery Plan for the subspecies should be considered and implemented, including in-situ and ex-situ conservation measures that guarantee its protection, conservation and recovery.